الشعــريـة في قصص "حافات حلم" لـ "إيناس البدران" - جري جاسم النداوي, محمد (Journal of College of Education, 2019)
This research focuses on the Poétique of the stories of "Bevels of the Dream" of the Iraqi literature "Inas Al-Badran", from the monitoring of the features that gave stories poetic characteristic, and gave the aesthetics of art contributed to deepen the meaning and breadth. This study focused on the structures and elements identified by the "poetry of the building", which included standing on (the narrator, narrated, and the narrateé ) and the "poetic language" on which the stories of the group were based.